355 Radical vs. simple hysterectomy: a retrospective study on the survival outcomes of cervical cancer patients. (13th November 2020) - Rivera, R; Cole, L
Abstract : Cervical cancer remains to be the most common gynecologic malignancy among Filipino women despite being a preventable disease. Radical hysterectomy with pelvic lymphadenectomy is considered the standard surgical treatment of choice for patients with cervical cancer confined to the cervix up to the upper vagina. However, recent studies show that a less radical approach can be offered to these patients with comparable outcomes to radical hysterectomy, but with lesser perioperative and post-operative morbidity. The purpose of this study was to compare the outcomes in terms of recurrence and survival among cervical cancer patients who underwent simple hysterectomy and radical hysterectomy seen in a tertiary government hospital. Records of all cervical cancer patients who underwent radical hysterectomy and simple hysterectomy for the past ten years were reviewed. The incidence of cervical cancer patients who underwent simple hysterectomy from 2009–2018 is 0.37 per 100 person years or 0.592:16, lower than 1:16 ratio from 1964–1974, as reported by Manalo and Sotto.1Only 9 out of 42 patients who underwent simple hysterectomy had cervical cancer screening within 1 year prior to surgery. The most common indication for surgery was myoma uteri. Those who underwent radical hysterectomy had better recurrence free survival and overall survival than those who had simple hysterectomy, but among low risk patients, those with 2 cm or less tumor size with no other risk factors, there was no significant difference in survival outcomes between the two groups.